Advances in motivation in sport and exercise - Roberts, Glyn C.; Treasure, Darren C. 1965- (Human Kinetics, 2012)
dvances in Motivation in Sport and Exercise, Third Edition, presents the most current information in sport and exercise motivation, including discussion of new research surrounding self-determination theory and goal achievement theory, traditional topics of goal setting and self-efficacy, and newer areas of attention such as passion and perfectionism. Readers not only will gain knowledge in one of the leading areas of sport psychology research but also learn how the research can inform their current practice. In this third edition, editors Glyn Roberts and Darren Treasure, along with a highly respected team of contributors, offer sport and exercise psychology researchers and students the most up-to-date review of the state of research in motivation. As in previous editions, the text chronicles the growth of motivation research and its role in physical activity, exercise, and sport. The star team of contributors offers thoughtful discussion of key issues and findings for readers to consider and insight into both the conceptual understanding of motivation and its application. Advances in Motivation in Sport and Exercise, Third Edition, begins by introducing readers to new trends and interpretations in motivational theory. Each chapter of the text discusses a unique motivational theory and its contemporary contribution to the field of knowledge. Whether research or practically inclined, readers will be enlightened through the use of these features: Presentation of differing perspectives and approaches that make up the current state of research in the most vibrant of topics in sport and exercise psychology; Future Directions for Research and Practical Applications sections at the end of each chapter that help demonstrate how the chapters' content is applied to real-world practice; An extensive reference list that serves as a tool for finding further resources and continuing study of motivation. The third edition of Advances in Motivation in Sport and Exercise helps readers learn how the theories of motivation can be applied in exercise, sport, and physical activity contexts. Thoughtfully compiled by a respected editor and contributor team, this comprehensive text serves as a review of current research and a resource for further study and applications for researchers, students, and practitioners.